Preservation of primary second molar for agenesis substitute with mineral trioxide aggregate - Salcedo Rioja, Rita (2009)
The purpose of this article was to report a clinic case of a female patient of 10 years old, which was performed pulpectomy in the tooth 75 with Mineral Trioxide Aggregate (MTA). In this article was used as for definitive obturation the Mineral Trioxide Aggregate (MTA), in order to preserve the tooth as long as possible due to the agenesis of the substitute. The tooth was clinically asymtomatic and radiographs showed a progressive repair of the apical lesion after the use of the mineral trioxide aggregate (MTA).